An Analysis of Directive Speech Acts in â€œXO, Kittyâ€ Television Series - Kristin Enjelina Sidabutar; Mhd. Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research aimed to revealed the types of directive speech act in â€œXO, Kittyâ€ Television series. Directive speech acts is about getting other people to do some certain actions that the speaker intended to, and it has several types which are commanding, requesting, asking, permitting, advising, inviting, and prohibiting (Searle, 1979). Also, descriptive qualitative research theorized by Creswell (2014) was applied in this research. In addition, the observational method and non-participatory technique by Sudaryanto (2015) were applied for collecting the data. Next, analyzing data was done by applying the â€œMetode padanâ€ and â€œTeknik pilah pembedaâ€ by Sudaryanto (2015). The result of this research showed that there were seven types of directive speech act revealed with 14 data found consisted of 2 data of commanding, 2 data of requesting, 4 data of asking, 1 data of permitting, 2 data of advising, 2 data of inviting, and 1 data of prohibiting. Last, the highest type of directive speech act found in the research was asking, and the least found were permitting and prohibiting.